Age-Friendly Public-Space Retrofit in Peri-Urban Villages Using Space Syntax and Exploratory Factor Analysis - Qin Li; Zhenze Yang; Jingya Cui; Xingping Wu; Jiao Liu; Wenlong Li; Yijun Liu (Buildings)
Population ageing is revealing acute mismatches between inherited village layouts and older residents’ everyday needs in China’s peri-urban fringe. This study combines space-syntax diagnostics with an exploratory factor analysis to create a building-oriented retrofit workflow. Using Liulin Village, Beijing, as a test bed, axial-line modelling pinpoints the low-integration alleys and mono-functional retail strips, while elder-user surveys distil four latent demand factors, led by personal convenience. Overlaying these two layers highlights the “high-demand/low-fit” segments for intervention. Prefabricated 3 m × 6 m health kiosks, sunrooms and rest pergolas—constructed from light-gauge steel frames and assembled with dry joints—are then inserted along a newly permeated corridor–core walking loop. The modules follow a 600 mm dimensional grid and can be installed or removed within a single working day, cutting the on-site labour by roughly one-third relative to that required for conventional masonry kiosks and enabling their future relocation or reuse. The workflow shows how small-scale, low-carbon building interventions can simultaneously improve accessibility, social interaction and functional diversity, providing a transferable template for ageing-responsive public-space retrofits in rapidly transforming village contexts.